Pertanggungjawaban Pengelola Tpa Terhadap Pencemaran Udara Yang Berdampak Pada Kesehatan Masyarakat: Studi Di Desa Anjani, Kecamatan Suralaga, Kabupaten Lombok Timur - Gita Alit Srinadi, Ida Ayu; Mustafa Umami, Allan (Private Law, 2024)
This research aims to analyze the “Responsibility of Landfill Managers for Air Pollution Impacting Public Health: A Study in Anjani Village, Suralaga Subdistrict, East Lombok Regency." The study employs legal, conceptual, and sociological approaches. The research utilizes a normative empirical method with descriptive analysis using qualitative methods obtained through interviews, observations, and documentary studies. The findings reveal that: (1) The landfill management regulations in Anjani Village are not implemented in accordance with applicable laws. (2) The impacts of air pollution extend beyond public health, affecting agriculture and farm in the vicinity of the landfill. (3) The accountability of landfill managers has not been fully implemented, both in terms of preventive and repressive law enforcement as well as administrative, civil, and criminal sanctions. Instead, landfill managers have opted for non-litigation negotiations to address the issue, primarily by extinguishing fires to mitigate the adverse effects on surrounding communities.